Pengaruh Kepribadian Proaktif dan Berbagi Pengetahuan terhadap Perubahan Sosial dan Implikasinya pada Kinerja Guru SD Swasta di Kota Serang - basrowi; Syabarrudin, Agus; susilawati; mutiah, eva (Center of Language and Cultural Studies, 2023)
The progress of education is closely related to the process of delivering information and knowledge to students optimally and how the supporting components in it can work properly. One important component in teaching and learning is teacher performance. The teacher is the key to the implementation of the teaching and learning process and the success of achieving learning outcomes in the school environment. For this reason, teacher performance needs to be improved to be able to motivate students in achieving maximum learning outcomes and to pay attention to the supporting factors for improving teacher performance so that the teaching and learning process can be carried out properly.The purpose of this study was to analyze the influence of proactive personality and knowledge sharing on social change and the implications for the performance of private elementary school teachers in Serang. The method used is quantitative, with a survey approach. Data collection techniques used questionnaires compiled by researchers based on the dimensions and indicators put forward by previous experts. The scale used is a Likert scale with five alternative answers. Based on the results of the analysis, it can be concluded that there is a significant influence between proactive personality and knowledge sharing on social change during a pandemic and the implications for teacher performance.